The Influence of Managerial Strategy and Political Connections and Company Size on Company Value - Saraswati , Wiwik; Sukoharsono, Eko Ganis; Saraswati , Erwin; Prastiwi , Arum (The International Journal of Accounting and Business Society, 2022)
Purpose - This study aims to test the Influence of Managerial Strategy, Political Connections, and company size on Company Value using secondary data on banking companies listed on the Indonesia Stock Exchange from 2013 to 2021.  Design/Methodology/approach—The sample selection method used purposive sampling with several criteria, resulting in 383 participants. In addition, this study used simple and multiple linear regression analysis techniques. Finding—The results showed empirical evidence that a banking company's managerial strategy cannot increase its value. Political connections also negatively affect company values. Political connections tend to get convenience facilities from the government to reduce the company's value. The size of the company can increase its value.  Practical implications—This research can also provide input into making policies and regulations in Indonesia regarding managerial strategies, political connection practices, and company sizes related to company values. Originality/value—This research has implications for theoretical enrichment. The agency is mainly concerned with the performance of companies with political connections. In addition, it enriches stakeholders' theories about managerial strategies for company value by increasing company investment. Keywords — Managerial strategy, Political Connections, Company Size, Company Value Paper Type: Quantitative Research